2023
DOI: 10.55324/josr.v2i3.726
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Mental Health Literacy to Help-Seeking Behavior: Systematic Review

Abstract: Mental health is an important aspect in realizing overall health. It is estimated that one in four people will suffer from a mental disorder during their lifetime. There are approximately 450 million people suffering from mental and behavioral disorders worldwide where about 85% of people with severe mental disorders in developing countries do not receive treatment for their disorders. This study aims to determine the relationship between mental health literacy and help-seeking behaviors. This research method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Information about mental health could be part of mental health literacy. Past studies showed the impact of mental health literacy in increasing help-seeking attitudes and behavior (Maya, 2020;Iswanto & Ayubi, 2023). Jorm (2020) explained that mental health literacy could support the skill to recognize, manage, and prevent mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Information about mental health could be part of mental health literacy. Past studies showed the impact of mental health literacy in increasing help-seeking attitudes and behavior (Maya, 2020;Iswanto & Ayubi, 2023). Jorm (2020) explained that mental health literacy could support the skill to recognize, manage, and prevent mental health problems.…”
Section: Discussionmentioning
confidence: 99%